2022
DOI: 10.1111/jvim.16483
|View full text |Cite
|
Sign up to set email alerts
|

Expression of adipokines and adipocytokines by epidural adipose tissue in cauda equina syndrome in dogs

Abstract: Background: Compression of epidural adipose tissue (EAT) within the scope of cauda equina syndrome (CES) could lead to an enhanced expression of inflammatory mediators, possibly contributing to pain amplification in dogs. Objectives:To analyze expression of inflammatory adipo(-cyto)kines within the EAT of dogs with CES.Animals: Client-owned dogs: 15 dogs with CES and 9 dogs euthanized for unrelated medical reasons (controls).Methods: Prospective, experimental study. Epidural adipose tissue and subcutaneous adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 72 publications
(159 reference statements)
0
0
0
Order By: Relevance
“…The research conducted by Yang indicated that CXCL8 and CXCL11 might enhance the expression of inflammatory cytokines, promote the apoptosis of chondrocytes and inhibit the proliferation by affecting the JAK-STAT signaling pathway. The results suggest that JAK/STAT signaling pathway plays an important role in the pathogenesis of OA [ 52 ]. The PI3K/Akt signaling pathway is a very classical signaling pathway that can regulate cell growth, proliferation, differentiation, and other life processes.…”
Section: Discussionmentioning
confidence: 99%
“…The research conducted by Yang indicated that CXCL8 and CXCL11 might enhance the expression of inflammatory cytokines, promote the apoptosis of chondrocytes and inhibit the proliferation by affecting the JAK-STAT signaling pathway. The results suggest that JAK/STAT signaling pathway plays an important role in the pathogenesis of OA [ 52 ]. The PI3K/Akt signaling pathway is a very classical signaling pathway that can regulate cell growth, proliferation, differentiation, and other life processes.…”
Section: Discussionmentioning
confidence: 99%